2017
DOI: 10.1038/s41467-017-00751-w
|View full text |Cite
|
Sign up to set email alerts
|

Foxp3+ Tregs are recruited to the retina to repair pathological angiogenesis

Abstract: Neovascular retinopathies are major causes of vision loss; yet treatments to prevent the condition are inadequate. The role of regulatory T cells in neovascular retinopathy is unknown. Here we show that in retinopathy regulatory T cells are transiently increased in lymphoid organs and the retina, but decline when neovascularization is established. The decline is prevented following regulatory T cells expansion with an IL-2/anti-IL-2 mAb complex or the adoptive transfer of regulatory T cells. Further, both appr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
68
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(71 citation statements)
references
References 55 publications
3
68
0
Order By: Relevance
“…Further, we have previously demonstrated that CD5-2 exposure results in recruitment of a favourable population of CD8 + T cells into the tumour microenvironment [20]. In OIR, the recruitment and expansion of forkhead box P3 (FOXP3) + regulatory T cells can reduce vasoobliteration, neovascularisation and vascular leakage, and alter the activation state of microglia [48]. Thus, the mechanism underlying the CD5-2-mediated effects to 'normalise' the vasculature and regulate inflammation in the eye awaits further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Further, we have previously demonstrated that CD5-2 exposure results in recruitment of a favourable population of CD8 + T cells into the tumour microenvironment [20]. In OIR, the recruitment and expansion of forkhead box P3 (FOXP3) + regulatory T cells can reduce vasoobliteration, neovascularisation and vascular leakage, and alter the activation state of microglia [48]. Thus, the mechanism underlying the CD5-2-mediated effects to 'normalise' the vasculature and regulate inflammation in the eye awaits further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…To further confirm the role of Treg in neonatal heart regeneration, we purified 1 million FOXP3 + (hCD2 + ) Treg from the spleen of NOD. Foxp3 hCD2 mice for adoptive transfer via intraperitoneal injection as previously described 20 into NOD/SCID mice so the recipients only harbored Treg without other conventional T-cells (Fig 4A). By flow cytometric analysis on day 7 following adoptive transfer, we found that about 88% of total CD3 + CD4 + T-cells were hCD2 + Treg in the spleen and heart, respectively (Fig 4B).…”
Section: Resultsmentioning
confidence: 99%
“…Such cells could potentially be expanded in vitro and used for treatment. In fact, a single clone of Treg has been recently expanded in vitro and was successfully used to reduce inflammation and neovascularisation in diabetic retinopathy in mice model [30], suggesting that deciphering the clonotypic map of T-cells in AA would bring the field a step closer toward understanding the disease pathogenesis.…”
Section: Discussionmentioning
confidence: 99%